English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-18 13:13:03 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

s^2-8s-33
I assume you mean: s² - 8s - 33

let s² - 8s - 33 = 0

factorise,

s...........-11..........-11s
s...........+3............+3s
________________
s²..........-33...........-8s

therefore (s - 11)(s + 3) = 0

s - 11 = 0..........or.........s + 3 = 0
s = 11................or.............. = -3

2007-06-18 13:25:42 · answer #1 · answered by jurassicko 4 · 0 0

(s - 11).(s + 3)
Check
s.(s + 3) - 11.(s + 3)
s² + 3s - 11s - 33
s² - 8s - 33 (as required)

2007-06-19 03:29:55 · answer #2 · answered by Como 7 · 0 0

(s - 11) (s + 3)

2007-06-18 20:15:34 · answer #3 · answered by davemb78 2 · 0 0

fedest.com, questions and answers